Ex Vivo and In Vivo Properties of an Injectable Hydrogel Derived From Acellular Ear Cartilage Extracellular Matrix - Gong, Danni; Yu, Fei; Zhou, Meng; Dong, Wei; Yan, Dan; Zhang, Siyi; Yan, Yan; Wang, Huijing; Tan, Yao; Chen, Ying; Feng, Bei; Fu, Wei; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Extracellular matrix (ECM) hydrogels provide advantages such as injectability, the ability to fill an irregularly shaped space, and the adequate bioactivity of native matrix. In this study, we developed decellularized cartilage ECM (dcECM) hydrogels from porcine ears innovatively via the main method of enzymatic digestion and verified good biocompatible properties of dcECM hydrogels to deliver chondrocytes and form subcutaneous cartilage in vivo. The scanning electron microscopy and turbidimetric gelation kinetics were used to characterize the material properties and gelation kinetics of the dcECM hydrogels. Then we evaluated the biocompatibility of hydrogels via the culture of chondrocytes in vitro. To further explore the dcECM hydrogels in vivo, grafts made from the mixture of dcECM hydrogels and chondrocytes were injected subcutaneously in nude mice for the gross and histological analysis. The structural and gelation kinetics of the dcECM hydrogels altered according to the variation in the ECM concentrations. The 10 mg/mL dcECM hydrogels could support the adhesion and proliferation of chondrocytes in vitro. In vivo, at 4 weeks after transplantation, cartilage-like tissues were detected in all groups with positive staining of toluidine blue, Safranin O, and collagen II, indicating the good gelation of dcECM hydrogels. While with the increasing concentration, the tissue engineering cartilages formed by 10mg/mL dcECM hydrogel grafts were superior in weights, volumes, collagen and glycosaminoglycan (GAG) content compared to the dcECM hydrogels of 1mg/mL and 5 mg/mL. At 8 weeks after grafting, dcECM hydrogel grafts at 10 mg/mL showed very similar qualities to the control, collagen I grafts. After 12 weeks of in vivo culture, the histological analysis indicated that 10 mg/mL dcECM hydrogel grafts were similar to the normal cartilage from pig ears, which was the source tissue. In conclusion, dcECM hydrogel showed the promising potential as a tissue engineering biomaterial to improve the regeneration and heal injuries of ear cartilage.